Dimensions of forgiveness : psychological research & theological perspectives - Worthington, Everett L., Jr., 1946- (Philadelphia : Templeton Foundation Press, 1998)
The scientific study of forgiveness is a new approach to an age-old problem. For thousands of years, people have practiced forgiveness within religious systems. Now, the field of scholarly research of forgiveness reveals the beneficial aspects of the process.
The ethos of Christian forgiveness / Martin E. Marty -- The elements of forgiveness : a Jewish approach / Elliot N. Dorff -- Forgiveness as a method of religious coping / Kenneth I. Pargament and Mark S. Rye -- The victim role, grudge theory, and two dimensions of forgiveness / Roy F. Baumeister, Julie Juola Exline, and Kristin L. Sommer -- The pyramid model of forgiveness : some interdisciplinary speculations about unforgiveness and the promotion of forgiveness / Everett L. Worthington, Jr. -- Researching the process model of forgiveness within psychological interventions / Robert D. Enright and Catherine T. Coyle -- Science and forgiveness interventions : reflections and recommendations / Carl E. Thoresen, Frederic Luskin, and Alex H. S. Harris -- An annotated bibliography of research on forgiveness and related concepts / Michael E. McCullough, Julie Juola Exline, and Roy F. Baumeister -- Empirical research in forgiveness : looking backward, looking forward / Everett L. Worthington, Jr. -- Stations on the journey from forgiveness to hope / Lewis B. Smedes.
"'A Journey to Hope: a Research Workshop to Launch the John Templeton Foundations's Program to Encourage the Scientific Study of Forgiveness,' held at Hope College in Holland, Michigan"--P. ix.
Includes bibliographical references and index.
Keywords: Forgiveness -- Congresses; Forgiveness -- Religious aspects -- Congresses; Adaptation, Psychological; Interpersonal Relations; Religion and Psychology